2007
DOI: 10.4315/0362-028x-70.9.2148
|View full text |Cite
|
Sign up to set email alerts
|

Physical Adsorption of Aflatoxin B1 by Lactic Acid Bacteria and Saccharomyces cerevisiae: A Theoretical Model

Abstract: The ability of lactic acid bacteria (LAB) and Saccharomyces cerevisiae to remove aflatoxin B1 (AFB1) from liquid medium was tested. The experimental results indicated that (i) AFB1 binding to microorganisms was a rapid process (no more than 1 min); (ii) this binding involved the formation of a reversible complex between the toxin and microorganism surface, without chemical modification of the toxin; (iii) the amount of AFB1 removed was both toxin- and bacteria concentration-dependent; and (iv) quantitatively s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
91
1
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(106 citation statements)
references
References 16 publications
7
91
1
7
Order By: Relevance
“…Then, the bacteria were incubated for 30 min at 37°C and pelleted by centrifugation. The supernatant was collected for free AFB 1 analysis by HPLC according to Bueno et al (2007). AFB 1 bound to cells was calculated as the difference between the total AFB 1 and the amount of free AFB 1 .…”
Section: Mechanism Proposed For the Interaction Between Aflatoxin B 1mentioning
confidence: 99%
See 3 more Smart Citations
“…Then, the bacteria were incubated for 30 min at 37°C and pelleted by centrifugation. The supernatant was collected for free AFB 1 analysis by HPLC according to Bueno et al (2007). AFB 1 bound to cells was calculated as the difference between the total AFB 1 and the amount of free AFB 1 .…”
Section: Mechanism Proposed For the Interaction Between Aflatoxin B 1mentioning
confidence: 99%
“…The first step in this direction is the selection of the most efficient microorganism for AFB 1 removing and while many researchers have assayed LAB and yeast with AFB 1 binding abilities (Ciegler et al, 1966;El-Nezami et al, 1998;Gourama & Bullerman, 1995;Line et al, 1994;Oatley et al, 2000) no clear mechanism for this effect has been provided. Thus, this selection frequently is performed using a single concentration of AFB 1 , but we demonstrated that the microorganism efficiency may change when the mycotoxin concentration is modified (Bueno et al, 2007;Pizzolitto, 2011), therefore the microorganism selected could not be the most competent. In this context, we investigated the nature of the interaction between different microorganisms and AFB 1 molecule, which led us to develop a model to explain the binding of AFB 1 by LAB and Saccharomyces cerevisiae strains.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…The beneficial effects of Saccharomyces cerevisiae in management of aflatoxin B1 toxicity has also been evaluated in broilers [106] and Quails [107]. Bueno et al [108] has also demonstrated that Saccharomyces cerevisiae is an important and efficient micro-organism in aflatoxin B1 quenching. Moreover, it is suggested that Saccharomyces cerevisiae cell wall have glucan, they reduce the frequency of micro nuclei induced by cyclophosphamide.…”
Section: Saccharomyces Cerevisiaementioning
confidence: 99%